DESCRIPTIVE STUDY ON SUICIDE ATTEMPTERS ATTENDING CONSULTATION-LIAISON PSYCHIATRY SERVICES AT A TERTIARY CARE HOSPITAL - K, Pugazhendhi; BHARATHI K; BALAMURUGAN K; J, Ravishankar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Suicidal attempts are more common than suicides. Knowing the sociodemographic profile of patients, psychological causes, and mode of attempts helps gain insight into suicide attempts. This study aims to describe the profile of suicide attempters attending consultation-liaison psychiatry services. Methods: This was a prospective observational study conducted at the psychiatry clinic, Government Villupuram Medical College and Hospital, Tamil Nadu on suicide attempters between June 2019 and November 2019. Beck’s suicide intent scale was used to assess the level of intent. Results: Of the total of 610 study individuals, the mean age was 28.73±11.73 years, majority were females (57.70%), suicide attempt was more in young adults (59.18%), more in married (64.91%), more in those with secondary school education (54.91%), and more in skilled workers and homemakers. Poison consumption was the most common mode of suicide attempt (92.62%), predominantly insecticides. Alcohol intoxication (39.14%) was the most common psychiatric derangement. Interpersonal conflict (63.44%) was the most common precipitating factor. About 74.92% had less suicidal intent. Conclusion: Marital conflicts, interpersonal conflicts, and alcohol-related illnesses were the major precipitating factors. Restriction of the availability of alcohol and toxic insecticides can help reduce the incidence of suicide attempts and deaths. The promotion of healthy coping mechanisms and community-based mental care activities can help in suicide prevention.